The art is the cloth : how to look at and understand tapestries - Sidore, Micala; Bremer-David, Charissa (Atglen, Pennsylvania : Schiffer Publishing, Ltd., 2020)
This eye-opening guide from expert tapestry weaver and historian Sidore gives how-to strategies enabling nonweavers to notice and appreciate the meaning of these artworks. (Book jacket)
Foreword: Visual poetry -- Acknowledgments -- Introduction -- The elements of weaving -- Special materials -- Visual themes, adapting the past to the present -- Trompe l'oeil -- Directionality -- Textiles and identities, when textiles define a particular group -- Self-reference -- Historical self-reference -- The art in the cloth.
kunstcatalogus
Keywords: Textielkunst: Tapijtkunst: Ontwerpers. Designers. Overzichten